An experimental and numerical study on diesel injection split of a natural gas/diesel dual-fuel engine at a low engine load. (15th January 2018) - Yousefi, Amin; Guo, Hongsheng; Birouk, Madjid
Abstract: Natural gas/diesel dual-fuel combustion is currently one of the most promising LTC strategies for the next generation of heavy-duty engines. While this concept is not new and it has been deliberated lengthily in the past two decades, several uncertainties still exist. A major shortcoming of this concept is associated with its low thermal efficiency and high level of unburned methane and CO emissions under low engine load conditions. The present paper reports an experimental and numerical study on the effect of different injection strategies (single and two pulses injection of pilot diesel fuel) on the combustion performance and emissions of a heavy duty natural gas/diesel dual-fuel engine at 25% engine load. The results of single diesel injection mode showed that advancing diesel injection timing from 10 to 30 °BTDC reduced unburned methane and CO emissions by 62% and 61% and increased thermal efficiency by 6%; however, NOx emissions increased by 74%. In order to achieve NOx – CH4 and NOx – CO trade-off and increased thermal efficiency at low load conditions, the effect of split injection strategy was experimentally and numerically examined. The results of split injection mode revealed that split injection strategy considerably increases the in-cylinder peak pressure compared to that of single injection (10 °BTDC). The results showed also that the heat release produced by the first injection of diesel fuel considerably increased the in-cylinder charge temperature before the start of the second injection. The flame zone of the split injection mode is markedly higher than that of the single injection due to larger heat release produced during the first injection which promotes the combustion of the second one. When the first injection timing is close to the second injection timing, the MPRR of split injection mode is higher than that of single injection (10 °BTDC). However, further advancing of the first injection timing continuously decreased the MPRR. OH radical analysis showed that for advanced first injection timings (38–50 °BTDC), the overall growth rate of OH radical becomes slower and its distribution is narrower as indicated by the wider non-reactive blue zones compared with those observed at a late first injection timing in the initial stages of combustion. However, OH radicals gradually grow during last stages of combustion in the expansion stroke, indicating that a more premixed combustion takes place in these cases. For very advanced first injection timing of 55 °BTDC, the OH distribution is similar to that of the single injection mode with lower OH intensity at initial stages of combustion and they barely grow during the late expansion stroke. At this condition, the ignition of premixed mixture is mainly controlled by the second diesel fuel injection. The trade-off between NOx – CH4 and NOx – CO is achieved when applying split injection. Compared to single injection (10 °BTDC), the first injection timing of 50 °BTDC decreased unburned methane and CO emissions by 60% and 63%, respectively, and increased the thermal efficiency by 8.9%. However, NOx emissions were maintained at the same level as single injection mode (10 °BTDC).